The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults. (15th January 2023) - Li, Jia-Min; Yang, Han-Yu; Wu, Si-Han; Dharmage, Shyamali C.; Jalaludin, Bin; Knibbs, Luke D.; Bloom, Michael S.; Guo, Yuming; Morawska, Lidia; Heinrich, Joachim; Steve Hung Lam, Yim; Lin, Li-Zi; et al.
Abstract: Particulate matter (PM) exposure is associated to the adverse change in blood lipids. Vitamin D is beneficial to lipid metabolism, but whether vitamin D levels modifies the impact of air pollutants on lipids is unclear. The purpose of the study was to investigate if vitamin D modifies the associations of PM and serum lipids in young healthy people. From December 2017 to January 2018, a panel study with five once weekly follow-ups was conducted on 88 healthy adults aged 21.09 (1.08) (mean (SD)) years on average in Guangzhou, China. We measured serum lipids, serum 25-hydroxyvitamin D (25(OH)D) concentrations (440 blood samples in total), mass concentrations of particulate matter with diameters ≤2.5 μm (PM2.5 ), ≤1.0 μm (PM1.0 ), and ≤0.5 μm (PM0.5 ), and number concentrations of particulate matter with diameters ≤0.2 μm (PN0.2 ) and ≤0.1 μm (PN0.1 ) at each follow-up. Linear mixed-effect models were applied to assess the interaction of vitamin D and size-fractionated PM short-term exposure on four lipid metrics. We found the interactions between 25(OH)D and size-fractionated PM exposure on blood lipids in different lags (lag 3 days and 4 days). An interquartile range increase in PM2.5, PM1.0, PM0.5 were significantly associated with increments of 12.30%, 12.99%, and 13.66% in triglycerides (TGs) at lag 4 days at vitamin D levels <15 ng/mL group, respectively. Similar results were found for PN0.2, PN0.1 and low-density lipoprotein cholesterol (LDL-C). All the associations between size-fractionated PM and blood lipids were found null statistically significant in vitamin D levels ≥15 ng/mL group. Graphical abstract: Image 1 Highlights: Vitamin D modified the association between particulate matter (PM) and blood lipids. PM2.5, PM10, PM0.5 are associated with increments of TGs at vitamin D < 15 ng/mL group. PN0.2 and PN0.1 are associated with increments of LDL-C at vitamin D < 15 ng/mL group. No association is observed between PM and blood lipids at vitamin D ≥ 15 ng/mL group.